THER-25. IMMUNE ONCOLYTIC ADENOVIRUS FOR DIPG TREATMENT - Laspidea, Virginia (Neuro Oncol, 2019)
Diffuse intrinsic pontine glioma (DIPG) is an aggressive and incurable pediatric brain tumor that arises in the brainstem. The median overall survival is only one year being the standard of treatment radiotherapy. Oncolytic adenoviruses have emerged as a promising therapeutic option for DIPG due to their specificity to tumor cells. Our clinical experience has shown that stimulation of an immune response against the tumor by the adenovirus is important for the effectivity of this therapy. 4-1BB is a major costimulatory receptor promoting the survival and expansion of activated T cells, as well as the generation and maintenance of memory CD8+ T cells. Since CD8+ T cells play a pivotal role in tumor immunity, enhancing 4-1BB costimulation promotes the generation of antitumor immune responses. In order to improve the antitumor immune response induced by the adenovirus, we have engineered the costimulatory molecule 4-1BBL into the genome of Delta-24-RGD (Delta-24-ACT). Delta-24-ACT was able to infect and to express viral proteins in a dose-dependent manner in murine DIPG cell lines, NP53 and XFM in vitro and in vivo. Importantly, Delta-24-ACT exerts a significant antitumoral effect in vitro, being XFM the cell line with higher sensitivity to the virus (3 days-IC(50): 3.4 MOI). DIPGcells infected with Delta-24-ACT during 24 hours showed expression of 4-1BBL in the plasma membrane in around 50% of cells. Delta-24-ACT induced immunogenic cell death in DIPG cell lines showing a significant increase of calreticulin in the plasma membrane, the release of ATP and HMGB1, which are DAMPs able to trigger an adaptive immune response. All these results suggest that Delta-24-ACT is functional in DIPG models in vitro. We are currently, performing toxicity and efficacy in vivo experiments in orthotopic DIPG models. Further, in vivo studies will uncover of the suitability of this new virus for the treatment of DIPG.